Faktor yang Berhubungan dengan Penerimaan Terapi Pencegahan TB di Kabupaten Tegal - Safitri, Iski Nur; Martini, Martini; Adi, Mateus Sakundarno; Wurjanto, Moh. Arie (Jurnal Riset Kesehatan Masyarakat, 2023)
Household contacts of tuberculosis (TB) patients are at high risk of being infected with Mycobacterium tuberculosis and experiencing latent TB (ILTB) which can develop into active TB. ILTB management is an important point in the TB control strategy. There are no known factors related to the low TPT revenue in Tegal Regency so research needs to be done. The study aimed to find factors related to TPT acceptance in household contacts of TB patients in Tegal Regency. The type of research is observational analytic with a cross sectional design. The study population was household contacts of active TB patients in the Adiwerna, Slawi, and Bumijawa Health Center Work areas with a sample of 178 people taken by purposive sampling method. Frequency distribution analysis and chi-square test are used in data analysis. The independent variables include age, gender, education level, kinship of respondents with TB patients, level of knowledge, distance between residence to puskemas, and education about TPT from health workers, with the dependent variable being the acceptance of TB prevention therapy in household contacts of TB patients. The research has passed the ethical review with No. 182/EA/KEPK-FKM/2023. The results showed a relationship between sex (p = 0.010), education level (p = 0.043), level of knowledge (p = <0.001), distance between residence to puskemas (p = <0001), and education about TPT from health workers (p = 0.001) with TPT acceptance.  Meanwhile, the age variable (p = 0.082) and the kinship of respondents with TB patients (p = 0.054) there was no relationship with TPT acceptance. It can be concluded that of the 7 variables there are 5 variables related to TPT. Community health center should conduct education and counseling about TPT with the right methods to be able to increase public knowledge related to TPT.